2005
DOI: 10.3748/wjg.v11.i4.511
|View full text |Cite
|
Sign up to set email alerts
|

Herbal cardiotonic pills prevent gut ischemia/reperfusion-induced hepatic microvascular dysfunction in rats fed ethanol chronically

Abstract: These results suggest that CP prevents the gut I/R-induced hepatic microvascular dysfunction and hepatocellular injury. A reduction of inflammatory responses such as TNF-alpha production via reduction of blood endotoxin levels appears to be involved in the mechanisms. Chronic ethanol consumption enhances gut I/R-induced hepatic microvascular and hepatocellular injury. CP also attenuates an enhancement of gut I/R-induced responses by chronic ethanol consumption via the reduction of blood endotoxin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Several lines of data have accumulated so far in this field. To mention a few, for example, pretreatment with Cardiotonic Pills (CP, the major ingredients of which are DLA and SalB) attenuated the gut ischemia/reperfusion-induced leukocyte adhesion in the liver sinusoids and plasma TNF-α and endotoxin [16] , and diminished the thrombi induced by photochemical stimulation in rat mesenteric venules, as demonstrated in our previous study [17] . CP was reported to inhibit the expression of ICAM-1 and vascular cell adhesion molecule 1 (VCAM-1) in endothelial cells [18] .…”
Section: Compound Danshen Injection Improves Endotoxin-induced Microcmentioning
confidence: 88%
“…Several lines of data have accumulated so far in this field. To mention a few, for example, pretreatment with Cardiotonic Pills (CP, the major ingredients of which are DLA and SalB) attenuated the gut ischemia/reperfusion-induced leukocyte adhesion in the liver sinusoids and plasma TNF-α and endotoxin [16] , and diminished the thrombi induced by photochemical stimulation in rat mesenteric venules, as demonstrated in our previous study [17] . CP was reported to inhibit the expression of ICAM-1 and vascular cell adhesion molecule 1 (VCAM-1) in endothelial cells [18] .…”
Section: Compound Danshen Injection Improves Endotoxin-induced Microcmentioning
confidence: 88%
“…Besides the I/R in- jury, an immunological mechanism should attribute to the further injury [18,19] . Antioxidant treatments have been used successfully to decrease reperfusion injury in multiple organ systems such as heart [20] , bowel [21] and liver [22] . Combined with detorsion, it has been reported that allopurinol [23] and superoxide dismutase plus catalase [2] treatment caused a signifi cant rescue of testes' function after testicular torsion.…”
Section: Discussionmentioning
confidence: 99%
“…A number of clinical and physiological effects of PNS have recently been described, such as improvement of myocardial dysfunction in rats with burn injuries (Zhang et al, 2003), amelioration of hepatic microcirculatory disturbances (Park et al, 2005), attenuation of LPS-induced adhesion of leukocytes to the venular wall and suppression of CD11b/CD18 expression in rat neutrophils (Sun et al, 2006), and improvement of endothelial cell function (Chen et al, 2004). Cardiotonic pills (CP, a traditional Chinese medicine which contains PN, salvia miltiorrhiza, and borneol), which use PNS as major ingredients, attenuate adhesion of leukocytes to hepatic sinusoids after ischemia-reperfusion (I/R) in rats chronically fed with ethanol, as demonstrated in our previous studies (Horie et al, 2005). In general, it can be said that the cellular and molecular events which underlie the biological activity of the major components of PNS have attracted much attention in the past few years.…”
Section: Introductionmentioning
confidence: 78%